2006
DOI: 10.1021/es060426z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Modeling of Pathogen Fate and Transport

Abstract: A watershed-scale fate and transport model has been developed for Escherichia coli and several waterborne pathogens: Cryptosporidiumspp., Giardiaspp., Campylobacter spp, and E. coli O157:H7. The objectives were to determine the primary sources of pathogenic contamination in a watershed used for drinking water supply and to gain a greater understanding of the factors that most influence their survival and transport. To predict the levels of indicator bacteria and pathogens in surface water, an existing hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 32 publications
5
86
0
Order By: Relevance
“…Despite the relatively large impact of nonpoint source pollution on instream microbial concentrations, quantitative data describing microbial transport in surface water is sparse and limits the reliability of modeling efforts ( Jamieson et al 2004a;Dorner et al 2006;Pachepsky et al 2006;Arnone & Walling 2007;Benham et al 2008;Keller & Cavallaro 2008). Specifically, microbes are generally modeled as individual free cells of near-neutral buoyancy, doi: 10.2166/wh.2009.232 even though increasing evidence suggests that many microorganisms partition between a particle-associated and free (unassociated) phase (Ferguson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively large impact of nonpoint source pollution on instream microbial concentrations, quantitative data describing microbial transport in surface water is sparse and limits the reliability of modeling efforts ( Jamieson et al 2004a;Dorner et al 2006;Pachepsky et al 2006;Arnone & Walling 2007;Benham et al 2008;Keller & Cavallaro 2008). Specifically, microbes are generally modeled as individual free cells of near-neutral buoyancy, doi: 10.2166/wh.2009.232 even though increasing evidence suggests that many microorganisms partition between a particle-associated and free (unassociated) phase (Ferguson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dorner et al indicated previously the importance of the resuspension of microorganisms from stream sediments rather than land-based sources according to the hydrological simulation of Escherichia coli during storm events (4). The quantitative detection of pathogens in environmental sediments is thus crucial for assessing the health effects of exposure to pathogen-contaminated sediments or pathogen-resuspended water.…”
mentioning
confidence: 99%
“…High concentrations of pathogens, indicator microorganisms, and other colloids can be rapidly transported from agricultural fields, urban environments, and hillslopes to streams or locations of surface water storage by runoff water (Rahe et al, 1978;Heathwaite et al, 2005;Haygarth et al, 2006). Runoff has been reported to be the primary transport route for pathogen dissemination at the hillslope scale (Tyrrel and Quinton, 2003;Jamieson et al, 2004;Dorner et al, 2006). An understanding of processes that influence the transport of pathogens and indicator microorganisms in runoff water is therefore needed to assess and mitigate risks of microbial contamination of surface water supplies to human health.…”
Section: Introductionmentioning
confidence: 99%